UNVEILING THE DIVERGENT NEEDS IN THE QUEST FOR RESOLUTION: A SOCIOLOGICAL ANALYSIS OF THE 2016 DISPUTE BETWEEN THE ISLAMIC JIHAD FRONT AND ST. JAMES ALFEUS CHURCH IN YOGYAKARTA, INDONESIA - Aditya, Refan (Jurnal Sosiologi Reflektif, 2023)
In 2016, the Islamic Jihad Front (FJI) organized a demonstration against the installation of a monumental statue depicting the face of Jesus at St. James Alfeus Church, located in Sendangsari Village, Bantul, Yogyakarta Special Region, Indonesia. Despite the occurrence of this event some years ago, it is crucial to pursue a theoretical framework for analyzing this interfaith conflict in the field of Sociology of Religion. In light of this requirement, the objective of this study is to reassess the dispute between FJI and St. James Alfes Church by employing an onion clone conflict analysis that specifically examines the stances, desires, and requirements of both entities, namely the church and FJI. The research was undertaken using a process-tracing technique to gather extensive data on the causes and mechanisms of the dispute. The analytical results indicate that the disagreement did not facilitate integration due to FJI's refusal to comply with the requests of St. Yaobus Alfeus Church. Conversely, each participant possesses distinct demands and interests that are not mutually comprehensible, hence reducing the likelihood of integration. This study suggests that effectively addressing interfaith disputes may be achieved by identifying and comprehending the individual needs of each participant involved.Pada 2016 lalu, Front Jihad Islam (FJI) menggelar aksi memprotes pendirian patung besar wajah Yesus di Gereja St. Yakobus Alfeus, Desa Sendangsari, Bantul, Daerah Istimewa Yogyakarta, Indonesia. Meskipun peristiwa ini telah terjadi beberapa tahun silam, namun upaya untuk terus mencari kerangka teoritik untuk ‘membaca’ konflik lintas agama ini menjadi kebutuhan dalam studi Sosiologi Agama. Berdasarkan kebutuhan ini, penelitian ini bertujuan untuk membaca ulang konflik FJI dengan Gereja St. Yakobus Alfes melalui the onion clonflict analysis yang berfokus pada posisi, kepentingan, dan kebutuhan kedua belah pihak, yaitu gereja dan FJI. Penelitian ini dilakukan melalui process-tracing approach untuk mendapatkan data yang komprehensif tentang apa dan bagaimana konflik tersebut terjadi. Hasil analisis menunjukkan bahwa konflik tidak memunculkan peluang integrasi karena tidak diterimanya tuntutan dari FJI kepada Gereja St. Yaobus Alfeus. Pada sisi lain, masing-masing pihak memiliki kebutuhan dan kepentingan masing-masing yang tak bisa dipahami satu sama lain sehingga semakin memperkecil peluang integrasi. Penelitian ini selanjutnya memberikan rekomendasi bahwa penyelesaian konflik lintas agama dengan mengungkap masing-masing kebutuhan antar aktor akan berfungsi apabila kebutuhan tersebut dipahami dengan baik oleh masing-masing pihak.